Pyogenic Liver Abscess with No Predisposing Risk Factors. (4th September 2018) - Chadwick, Matthew; Shamban, Leonid; Neumann, Michael
Abstract : Pyogenic liver abscesses (PLA) are an uncommon cause of hospitalization in the United States. The majority of such cases are polymicrobial and are most commonly caused by seeding of infection from the biliary system. PLA is frequently associated with specific comorbidities such as diabetes mellitus, history of liver transplant, underlying hepatobiliary, or pancreatic disease. Herein, we describe a 47-year-old healthy male with no known risk factors associated with PLA who presented to the hospital with acute fever, abdominal pain, and dark colored urine. Initially the patient had a negative right upper quadrant ultrasound. However, the patient continued to have persistent fevers and abnormal liver biochemistries with negative liver serology that led to checking a magnetic resonance cholangiopancreatography which suggested multiple liver abscesses. Computer tomography guided aspiration revealed a monobacterial Streptococcus species within the abscess, which is commonly associated with arterial bacteremia as a source of PLA. Arterial bacteremia is one of most rare causes of PLA. The patient's septic workup was negative for any source of infection. This case demonstrates a patient with no risk factors who was diagnosed with PLA caused by apparent arterial bacteremia with no clear source of infection.